Diet normalization or caloric restriction as a preconception care strategy to improve metabolic health and oocyte quality in obese outbred mice - Anouk Smits; Waleed F. A. Marei; Diane De Neubourg; Jo L. M. R. Leroy (BMC, 2021)
Abstract Background Maternal metabolic disorders are linked to reduced metabolic health and oocyte quality. Obese women are advised to lose weight before conception to increase pregnancy chances. However, as human studies show no univocal guidelines, more research is necessary to provide fundamental insights in the consequences of dietary weight loss on oocyte quality. Therefore, we investigated the impact of diet normalization or calorie restricted diet for two, four or six weeks, as preconception care intervention (PCCI), in obese mice on metabolic health and oocyte quality. Methods Outbred female mice were fed a control (CTRL) or high-fat (HF) diet for 7 weeks (7w). Afterwards, HF-mice were put on different PCCIs, resulting in four treatment groups: 1) control diet up to 13w, 2) HF diet up to 13w (HF_HF), switch from a HF (7w) to 3) an ad libitum control diet (HF_CTRL) or 4) 30% calorie restricted control diet (HF_CR) for two, four or six weeks. Body weight, metabolic health, oocyte quality and overall fertility results were assessed. Results Negative effects of HF diet on metabolic health, oocyte quality and pregnancy rates were confirmed. HF_CTRL mice progressively improved insulin sensitivity, glucose tolerance, serum insulin and cholesterol from PCCI w2 to w4. No further improvements in metabolic health were present at PCCI w6. However, PCCI w6 showed best oocyte quality improvements. Mature oocytes still showed elevated lipid droplet volume and mitochondrial activity but a significant reduction in ROS levels and ROS: active mitochondria ratio compared with HF_HF mice. HF_CR mice restored overall insulin sensitivity and glucose tolerance by PCCI w4. However, serum insulin, cholesterol and ALT remained abnormal. At PCCI w6, glucose tolerance was again reduced. However, only at PCCI w6, oocytes displayed reduced ROS levels and restored mitochondrial activity compared with HF_HF mice. In addition, at PCCI w6, both PCCI groups showed decreased mitochondrial ultrastructural abnormalities compared with the HF_HF group and restored pregnancy rates. Conclusions Diet normalization for 4 weeks showed to be the shortest, most promising intervention to improve metabolic health. Most promising improvements in oocyte quality were seen after 6 weeks of intervention in both PCCI groups. This research provides fundamental insights to be considered in developing substantiated preconception guidelines for obese women planning for pregnancy.